Current fluid and blood product availability in veterinary setting: a survey of UK small animal practices. (16th October 2020) - Beeston, D.; Charnock, J.; Cook, S.
Abstract : Objectives: To investigate and discuss current fluid and blood products stocked in small animal practices in the UK. Methods: An online survey was circulated to small animal veterinary practices across the UK. The survey included questions regarding the level of hospital care provided, the type of fluid and blood component products stocked, the most frequently restocked products, and the available options in the event that blood products were required but not stocked. Results: There were 423 responses including 27 duplicates. The remaining 396 respondents represented a spectrum of practices including 19 referral practices. Crystalloids were stocked in all practices. Lactated Ringer's solution was the most frequently re‐stocked product in 355 of 396 (90%) of practices. Where synthetic colloids were stocked, gelatin‐based colloids (155/178 [87%]) were stocked in preference to hydroxyethyl starches (23/178 [13%]). Blood products were stocked by 81 of 396 (20%) of practices. If a blood product was required but not stocked, 31% of practices would use a pet blood banking service, 28% would use their own blood donors, and 21% would refer. Clinical Significance: This study provides an insight into the fluid and blood products stocked and used by a selection of veterinary practices within the UK and serves as a baseline for ongoing research and decision‐making in both veterinary practice and industry.